AL-QUR’AN DAN ETIKA DAKWAH VIRTUAL - Kumala, Nur (Jurnal Dakwah, 2020)
The current era of disruption makes it easier for humans to convey and receive new information, especially about religion. However, in fact there are still some people who shut themselves off to convey the goodness that they know. Seeing this condition and the massive radicalization that has occurred in the internet media, a solution is needed to answer it. This article, which is a qualitative type of research with literature study through a content analysis approach to the verses of the Koran, has resulted in a new understanding of the importance of virtual da'wah for the process of spreading the Rahmatan lil 'Alamin Islam to all people in the world, so that da'wah on the internet is not it only explains in terms of its superiority, but also the purpose of da'wah which must be developed with several ethics that must be considered according to the Qur'an, including media skills, scientific and moral credibility, as well as polite da'wah material, namely upholding compassion (not advocating let alone giving hate speech).Era disrupsi saat ini menjadikan manusia lebih mudah untuk menyampaikan dan menerima informasi baru, terutama tentang agama. Namun, kenyatannya masih terdapat beberapa orang yang menutup diri untuk menyampaikan kebaikan yang ia ketahui. Melihat kondisi demikian serta masifnya radikalisasi yang terjadi di media internet, maka dibutuhkan solusi untuk menjawabnya. Artikel ini yang merupakan penelitian jenis kualitatif dengan studi kepustakaan melalui pendekatan analisis isi terhadap ayat Al-Qur’an yang menghasilkan pemahaman baru terkait pentingnya dakwah virtual bagi proses penyebaran agama Islam yang Rahmatan lil ‘Alamin bagi seluruh umat di dunia, sehingga dakwah di internet tidak hanya menjelaskan dari sisi keunggulannya saja, tapi juga tujuan dakwah yang harus dikembangkan dengan beberapa etika yang harus diperhatikan menurut Al-Qur’an, diantaranya kecakapan bermedia, kredibiltas keilmuwan dan akhlak, serta materi dakwah yang santun, yaitu menjunjung tinggi rasa kasih sayang (tidak memprofokasi apalagi memberikan ujaran kebencian).